A three‐tier system for evaluation of organ procurement organizations' willingness to pursue and utilize nonideal donor lungs. Issue 3 (29th October 2020) - Halpern, Samantha E.; McConnell, Alec; Peskoe, Sarah B.; Raman, Vignesh; Jawitz, Oliver K.; Choi, Ashley Y.; Neely, Megan L.; Palmer, Scott M.; Hartwig, Matthew G.
Abstract : Lungs from "nonideal, " but acceptable donors are underutilized; however, organ procurement organization (OPO) metrics do not reflect the extent to which OPO‐specific practices contribute to these trends. We developed a comprehensive system to evaluate nonideal lung donor avoidance, or risk aversion among OPOs. Adult donors in the UNOS registry who donated ≥1 organ for transplantation between 2007 and 2018 were included. Nonideal donors had any of age>50, smoking history ≥20 pack‐years, PaO2 /FiO2 ratio ≤350, donation after circulatory death, or increased risk status. OPO‐level risk aversion in donor pursuit, consent attainment, lung recovery, and transplantation was assessed. Among 83916 donors, 70372 (83.9%) were nonideal. Unadjusted OPO‐level rates of nonideal donor pursuit ranged from 81 to 100%. In a three‐tier system of overall risk aversion, tier 3 OPOs (least risk‐averse) had the highest rates of nonideal donor pursuit, consent attainment, lung recovery, and transplantation. Tier 1 OPOs (most risk‐averse) had the lowest rates of donor pursuit, consent attainment, and lung recovery, but higher rates of transplantation compared to tier 2 OPOs (moderately risk‐averse). Risk aversion varies among OPOs and across the donation process. OPO evaluations should reflect early donation process stages to best differentiate over‐ and underperforming OPOs and encourage optimal OPO‐specific performance. Abstract : The authors characterize variability in the pursuit and use of nonideal donor lungs among US organ procurement organizations and propose a 3‐tier evaluation system for OPOs that provides a detailed performance breakdown for each stage of the donation process and actionable information to guide improvement.